(untitled) (Revista Geoaraguaia, 2020)
The Baghche Maryam (BM) granitoid body is located in the northern part of the Sanandaj-Sirjan zone (SSZ), NW Iran. The BM intrusion is composed of diorite, monzodiorite, syenite and granite with a calc-alkaline to alkaline affinity. Mafic minerals in the BM rocks are biotite and Amphibole. Amphiboles are calcic (magnesiohornblende). The emplacement pressure average of the BM intrusion for granite and diorite rocks is 2.14 and 2.33+0.6 kbar, respectively. During the evolution of this magmatic system to higher silica contents, there was an increase in the activity of oxygen and a decrease in the temperature and the emplacement depth from the monzogabbro-monzodiorite to granite rocks; this is consistent with the typical evolution of the granitoid rocks. The studied amphibole rims show the calculated higher temperature and pressure and low ƒO2 and H2O content than the core of amphiboles which reflects differences in emplacement depth and crystallization conditions.